Impact of colchicine on hs-CRP, neutrophil levels, neutrophil-to-lymphocyte ratio and major adverse cardiac events (MACEs) in Thai patients with acute coronary syndrome undergoing percutaneous coronary intervention - Wattanasiriporn, Wittawat; Rattanasidha, Paruj; Munirwan, Haris; Arayangkoon, Chantisa (Narra J, 2026)
Acute coronary syndrome (ACS) is strongly associated with inflammation, which contributes to plaque instability, thrombosis, and adverse cardiovascular outcomes. High-sensitivity C-reactive protein (hs-CRP), neutrophil count, and neutrophil-to-lymphocyte ratio (NLR) are inflammatory markers that have been associated with poor prognosis in patients with ACS. Colchicine has emerged as a potential adjunctive anti-inflammatory therapy in cardiovascular disease. This study aimed to evaluate the effects of colchicine on inflammatory markers and clinical outcomes in Thai patients with ACS undergoing percutaneous coronary intervention (PCI). This single-center, retro-prospective observational cohort study included adult patients with ACS who underwent PCI at Rajavithi Hospital, Bangkok, Thailand, in 2024. Patients were classified into colchicine and non-colchicine groups based on treatment exposure after PCI. Hs-CRP, neutrophil count, and NLR were assessed at baseline, 1 month, and 3 months. Major adverse cardiac events (MACE) during follow-up were also recorded. A total of 56 patients were included, comprising 38 in the colchicine group and 18 in the non-colchicine group. Compared with the non-colchicine group, the colchicine group showed significantly greater reductions from baseline to 3 months in hs-CRP levels (2.29±3.37 vs 0.45±1.03; p=0.044), neutrophil count (21.86±10.62 vs 4.13±12.92; p=0.001), and NLR (2.98±2.93 vs 1.68±3.60; p=0.025). No significant differences in MACE were observed between the two groups. This study highlighted that colchicine was associated with greater reductions in inflammatory markers during the early post-PCI period, although no significant difference in short-term clinical outcomes was identified. Larger prospective studies are needed to confirm these findings.